Expiry of medicines in supply outlets in Uganda - Josephine Katabaazi Nakyanzi; Freddy Eric Kitutu; Hussein Oria; Pakoyo Fadhiru Kamba
PROBLEM: The expiry of medicines in the supply chain is a serious threat to the already constrained access to medicines in developing countries. APPROACH: We investigated the extent of, and the main contributing factors to, expiry of medicines in medicine supply outlets in Kampala and Entebbe, Uganda. A cross-sectional survey of six public and 32 private medicine outlets was done using semi-structured questionnaires. LOCAL SETTING: The study area has 19 public medicine outlets (three non-profit wholesalers, 16 hospital stores/pharmacies), 123 private wholesale pharmacies and 173 retail pharmacies, equivalent to about 70% of the country's pharmaceutical businesses. Our findings indicate that medicines prone to expiry include those used for vertical programmes, donated medicines and those with a slow turnover. RELEVANT CHANGES: Awareness about the threat of expiry of medicines to the delivery of health services has increased. We have adapted training modules to emphasize management of medicine expiry for pharmacy students, pharmacists and other persons handling medicines. Our work has also generated more research interest on medicine expiry in Uganda. LESSONS LEARNED: Even essential medicines expire in the supply chain in Uganda. Sound coordination is needed between public medicine wholesalers and their clients to harmonize procurement and consumption as well as with vertical programmes to prevent duplicate procurement. Additionally, national medicine regulatory authorities should enforce existing international guidelines to prevent dumping of donated medicine. Medicine selection and quantification should be matched with consumer tastes and prescribing habits. Lean supply and stock rotation should be considered.